2020
DOI: 10.1016/j.jhep.2019.09.023
|View full text |Cite
|
Sign up to set email alerts
|

Role of locoregional therapies in the wake of systemic therapy

Abstract: Multiple systemic agents have recently been approved in the first-and second-line setting for hepatocellular carcinoma (HCC), increasing the therapeutic options for patients and treating physicians. The randomised controlled trials that led to these approvals were predominantly conducted in a population comprised of patients with advanced HCC. However, these trials also included a subset of patients who had progressed after locoregional therapies (LRTs), mostly transarterial chemoembolisation. With a greater n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 76 publications
(86 reference statements)
1
47
0
Order By: Relevance
“…Lenvatinib plus pembrolizumab has recently become a potent systemic combination therapy for unresectable HCC ( 6 ). In clinical practice, locoregional-systemic combinations are widely applied due to the overall control of tumor conditions ( 13 ). The result of a randomized clinical trial conducted by Ming Shi et al demonstrated that a combination of sorafenib plus HAIC using FOLFOX agents extends overall survival by 87.5% or 6.24 months compared to sorafenib alone in HCC patients with portal vein invasion ( 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…Lenvatinib plus pembrolizumab has recently become a potent systemic combination therapy for unresectable HCC ( 6 ). In clinical practice, locoregional-systemic combinations are widely applied due to the overall control of tumor conditions ( 13 ). The result of a randomized clinical trial conducted by Ming Shi et al demonstrated that a combination of sorafenib plus HAIC using FOLFOX agents extends overall survival by 87.5% or 6.24 months compared to sorafenib alone in HCC patients with portal vein invasion ( 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…Locoregional therapies, including transarterial chemoembolization (TACE) and ablations, are proposed to postpone disease progression ( Palmer et al, 2020 ). Therapy that combines TACE and RFA has been recommended and has proven to be an effective selection for intermediate and advanced HCC (Z. W. Peng et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Since HCCs are solely supplied by the hepatic artery, transarterial treatments have proven to be extremely effective in delivering targeted embolic therapies to tumors while preserving and minimizing exposure to the surrounding liver parenchyma, especially when performed in an extremely selective manner (Breedis and Young, 1954;Kerbel, 2008;Pillai et al, 2020). TACE is the most widely used therapeutic intervention for patients with intermediate-stage HCC (Palmer et al, 2020). There are four types of embolization used for HCC treatment in clinic: bland embolization, conventional TACE, drug-eluting bead chemoembolization (DEB-TACE), and TARE (Kritzinger et al, 2013;Kloeckner et al, 2020).…”
Section: Transarterial Chemoembolizationmentioning
confidence: 99%